2013
DOI: 10.1002/jmor.20142
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal morphology of the wild atlantic salmon (Salmo salar)

Abstract: The worldwide-industrialized production of Atlantic salmon (Salmo salar) has increased dramatically during the last decades, followed by diseases related to the on-going domestication process as a growing concern. Even though the gastrointestinal tract seems to be a target for different disorders in farmed fish, a description of the normal intestinal status in healthy, wild salmon is warranted. Here, we provide such information in addition to suggesting a referable anatomical standardization for the intestine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
83
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 52 publications
(95 reference statements)
15
83
0
3
Order By: Relevance
“…This is in agreement with findings for Atlantic cod (Peruzzi et al 2013). The numbers of pyloric caeca of farmed diploid salmon (range 50-62) found in our study overlap those reported for wild fish (range 55-75) (Løkka et al 2013). …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This is in agreement with findings for Atlantic cod (Peruzzi et al 2013). The numbers of pyloric caeca of farmed diploid salmon (range 50-62) found in our study overlap those reported for wild fish (range 55-75) (Løkka et al 2013). …”
Section: Discussionsupporting
confidence: 71%
“…With regard to Atlantic salmon, gut morphology of wild, diploid fish has been described (Løkka et al 2013), but information about the digestive system of farmed triploids is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…During the sampling procedure, macroscopic examination was performed, and pathological manifestations were registered. Samples were conserved in RNAlater and were collected from the second segment of midintestine (16), hereafter referred to as intestine, midkidney, and gills. In addition, gill samples designated for laser-capture microdissection were snap-frozen in liquid nitrogen for subsequent cryosectioning.…”
Section: Samplingmentioning
confidence: 99%
“…Measurement of the surface area of pyloric ceca is less feasible, as the high number of ceca makes surface measurement very time-consuming and the lengthy handling time would severely lower the quality of the preparations. Furthermore, to our knowledge, there is no correlation between surface area of pyloric ceca and body weight as proposed for the skin, mainly due to the high individual variation in the numbers of ceca (31). Instead, the mucins of the pyloric ceca are expressed per unit of weight of the organ.…”
Section: Methodsmentioning
confidence: 89%